Cathepsin S Is Involved in Th17 Differentiation Through the Upregulation of IL-6 by Activating PAR-2 after Systemic Exposure to Lipopolysaccharide from Porphyromonas gingivalis - Dekita, Masato; Wu, Zhou; Ni, Junjun; Zhang, Xinwen; Liu, Yicong; Yan, Xu; Nakanishi, Hiroshi; Takahashi, Ichiro (Frontiers in Pharmacology, 2017)
Positive links have been found between periodontitis and numerous diseases in humans via persistent inflammation throughout the body. However, the main factors responsible for maintaining this pro-inflammatory condition are poorly understood. The spleen, the largest secondary immune organ, is a central hub regulating the immune response/inflammation due to the dendritic cell (DC) response to CD4+ T cell subtype differentiation, and lysosomal proteinase cathepsin S (CatS) is known to be involved in DC functions. In the present study, we found that CatS-induced IL-6 production by splenic DCs subsequently promotes Th17 differentiation, in response to systemic exposure to lipopolysaccharide derived from Porphyromonas gingivalis (PgLPS). The population of CD11c+ DCs was significantly increased in the splenic marginal zone (MZ) locally of wild-type (DBA/2) mice with splenomegaly but not in that of CatS deficient (CatS-/-) mice after systemic exposure to PgLPS for 7 consecutive days (5 mg/kg/day, intraperitoneal). Similarly, the population of Th17+CD4+ T cells was also significantly increased in the splenic MZ of wild-type mice but not in that of CatS-/- mice after PgLPS exposure. Furthermore, the increase in the Th17+ CD4+ T cell population paralleled increases in the levels of CatS and IL-6 in CD11c+ cells in the splenic MZ. In isolated primary splenic CD11c+ cells, the mRNA expression and the production of IL-6 was dramatically increased in wild-type mice but not in CatS-/- mice after direct stimulation with PgLPS (1 µg/ml), and this PgLPS-induced increase in the IL-6 expression was completely abolished by pre-treatment with Z-Phe-Leu-COCHO (Z-FL), the specific inhibitor of CatS. The PgLPS activated protease-activated receptor (PAR) 2 in the isolated splenic CD11c+ cells was also significantly inhibited by CatS deficiently. In addition, the PgLPS-induced increase in the IL-6 production by splenic CD11c+ cells was completely abolished by pre-treatment with FSLLRY-NH2, a PAR2 antagonist, as well as Akti, a specific inhibitor of Akt. These findings indicate that CatS plays a critical role in driving splenic DC-dependent Th17 differentiation through the upregulation of IL-6 by activating PAR2 after exposure to components of periodontal bacteria. Therefore, CatS-specific inhibitors may be effective in alleviating periodontitis-related immune/inflammation.